PENGARUH CURRENT RATIO, RETURN ON ASSET, DAN DEBT TO EQUITY RATIO TERHADAP PERUBAHAN LABA PADA PERUSAHAAN SUB SEKTOR PERDAGANGAN RITEL DI BURSA EFEK INDONESIA - Talitha Ihram; Dwi Susilowati; Nadi Hernadi Moorcy (MEDIA RISET EKONOMI [MR.EKO], 2022)
The Purpose of this study was to determine the effect of the Current Ratio, Return On Asset, and Debt to Equity Rasio partially on changes in porfit of retail trading Sub-Sector Companies on the Indonesia Stock Exchange. The data used are sources that already exist, both internal and external. The data can be accessed on the internet and information publications. The population in this study were seventeen companies and the samples  used was six companies that listed on the Indonesia Stock Exchange. The data analysis method used is multiple linear regression. The results of the analysis show that the variable Return On Asset has a signifficant effect on changes in porfit, while Current Ratio and Debt to Equity Ratio have no significant effect on changed in profit.